Description scleractinian coral from Miang Island, East Kalimantan - Rosdianto Rosdianto; Sayyid Afdhal El Rahimi; Adrian Kryk; Sulastri Arsad; Oktiyas Muzaky Luthfi; M Azurea Bahri Luthfi (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2022)
The exact number of coral species in Indonesia is not unclear yet, in 2002 the coral taxonomist, JEN Veron, stated 590 species, and it was supported by an Indonesian coral taxonomist, Suharsono, eight years later. The current coral species data is 605 but it is from Coral Triangle Region area (CT). The eastern of Indonesia, which is located in the Coral Triangle Region, has received a lot of attention from coral researchers, due to coral species that have been described. On the other hand, the coral reef from the western part of Indonesia, including in the East Kalimantan, has not been explored much in recent times. Through the ecoregion view, E. Kalimantan region is clustered into ecoregion 43 (Sulu Sea) which has 540 coral species. Miang Island is one of the inhabited islands from E. Kalimantan, and has an unexplored coral reef ecosystem. The method had been used in this research is descriptive, which uses photos of live corals to describe colony characteristics corals. The results of the study have described 36 species of coral and several invertebrates that make up coral reefs on Miang Island.Keywords:Hard coralAcroporaPoritesIdentificationPulau Miang